T-Cell Non-Hodgkin Lymphoma of the Ileum Presenting as Perforation and Peritonitis: A Case Report - Tian, Yong; Li, Chuanfang; Tian, Rusong; Tian, Qingming; Qiao, Song (Frontiers in Surgery, 2022)
Background Non-Hodgkin lymphoma (NHL) of the ileum presenting as perforation and peritonitis is a rare disease, derived from intestinal intraepithelial T lymphocytes.The degree of malignancy is extremely high. The pathogenesis of ileal perforation caused by NHL remains unclear, Chromosome and immune system abnormalities, which may be related to NHL, and are indistinguishable from other benign and malignant conditions and clinically nonspecific. Case report We here describe an 84-year-old male with abdominal pain for four days, aggravating for three hours. The pain at the upper abdominal region was initially considered as gastrointestinal perforation, and was initially located at the upper abdomen area. He had persistent insidious pain, accompanied by nausea, vomiting and fever. Physical examination indicated that the patient had pain all over the abdomen, rebound pain and muscle tension, and bowel sounds were reduced on auscultation. The abdominal CT scan showed free gas in the abdominal cavity.The patient was diagnosed with peritonitis due to hollow viscus perforation.We promptly performed exploratory laparotomy.Intraoperative findings showed perforations in the ileum that were approximately 40 cm from the ileocecal region and 3-8 mm in size. Segmental distribution was observed, and the intestinal contents overflowed with purulent moss around the perforation surface. Resection and ileostomy were performed,and the clinical histopathological examination confirmed T-cell lymphoma. Conclusion: Timely emergency surgery is the key to treatment of the ileal perforation caused by T-cell lymphoma. Resection and ileostomy were performed as intervention measures, and the subsequent histopathological examination manifested T-cell lymphoma. The patient was advised to visit the oncology department for further chemotherapy.